Influence Of Firm Resources, Organizational Characteristics and Macro-Environment on Export Performance of Small and Medium Manufacturing Enterprises in Nairobi City County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2020)
The broad objective of this study was to determine the joint influence of firm resources, organizational characteristics, and macro environment on export performance of small and medium manufacturing enterprises in Nairobi city county, Kenya. A conceptual model was developed, and from it, a hypothesis was formulated to test the joint influence of firm resources, organizational characteristics, and macro environment on export performance. The study is anchored on four theories; the Resource Based Theory, Porters Theory of competitive advantage, The Industrial Organization Theory and Firm Internationalization Theory. The research was a cross-sectional survey of 265 companies in Nairobi City County, chosen from a population of 853 companies. The unit of analysis was the SMME involved in exporting. The Cronbach alpha coefficient was used to evaluate internal consistency and homogeneity among the study variables. Out of the 265 firms sampled, 238 completed the questionnaire resulting in 89.1 percent response rate. The responses were then used to evaluate the hypothesis of the research. A level of five percent was chosen when testing the coefficients’ importance. The findings from the hypothesis was that, jointly,firm resources,organizational characteristics and macro-environment influence export performance. The study has contributed to theory, policy, management and practice, industry and methodology. Based on the research results, the national and county governments need to formulate legislation and policies that promote the growth of small and medium-sized enterprises, such as creating an appropriate atmosphere for SMMES to acquire credit and recommending appropriate and effective production processes. Further, stakeholders in export promotion should appreciate and place an emphasis on the importance and impact of the economic factor in the macro-environment to guide existing and potential investors in manufacturing and exporting sector. The research had certain constraints primarily due to the categorization of the enterprises by the various government agencies and stakeholders. The limitations however did not have significant effect on the findings. Future studies should address the scope and geographical coverage of SMMEs.